LEGAL BASIS OF SUSTAINABLE DEVELOPMENT OF AGRICULTURE AND WAYS OF IMPROVEMENT (International journal of artificial intelligence, 2025)
Agriculture is one of the main sectors of the economy of every country, and its sustainable development directly affects food security, population well-being and economic growth. A solid legal framework is necessary for the effective organization of agricultural activities. This article discusses the legal framework for agricultural development, existing problems and ways to improve them.